Current Understanding of Natural Antibodies and Exploring the Possibilities of Modulation Using Veterinary Models. A Review - Reyneveld, G. IJsbrand; Savelkoul, Huub F. J.; Parmentier, Henk K. (Frontiers in Immunology, 2020)
Natural antibodies (NAbs) are defined as germline encoded immunoglobulins found in individuals without (known) prior antigenic experience. NAbs bind exogenous (bacterial) and self-components and have been found in every vertebrate species tested. NAbs likely act as a first-line immune defence against infections, but also clear self-neo-epitopes, apoptotic and necrotic cells: so called natural auto-antibodies (NAAb). IgM and IgG NAbs and their implications in health and disease are relatively well described in man and mice. NAbs are present in veterinary species, but their relations with diseases and disorders are much less known. Also, there little is known of IgA NAbs. IgA is the most abundant immunoglobulin with essential pro-inflammatory and homeostatic properties urging for more research on the importance of IgA NAbs. Since NAbs in man were shown to fulfil important functions in health and disease, their role in health of veterinary species should be investigated. Also it is unknown whether levels of NAb isotypes and idiotypes can and should be modulated. Veterinary species as models of choice fill in a niche between mice and (non-human) primates, and the study of NAbs in these species may add valuable new insights that will likely add to improved health management.. Here, possibilities of intravenous immunoglobulin administration, targeted immunotherapy, immunization, diet and genetic modulation are discussed. Within the One Health concept, findings from veterinary studies can be related to human studies and vice versa so that both fields will mutually benefit. This will lead to a better understanding of NAbs: their origin, activation mechanisms, and their implications in health and disease, and will lead to novel health management strategies for both human and veterinary species.